Analisa Plat Lantai Dasar Gedung Serbaguna Politeknik Negeri Balikpapan - Mahfud Mahfud (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2016)
AbstractMany way of to be able to know density of land ground. One of the way that test of sand cone as according to conducted by examination at project o public building politectic state of Balikpapan. This test is conducted to get dry land volume to weight original land;ground and also land;ground result of work of condensation, and also to know difference plate restating dance grade on slab and suspended. Heavy value obtained dry land volume through attempt of this cone sand, is used to evaluate result of work condensation of expressed field in Degree of Condensation (Degree Of Compaction) in set of % with minimum value 95 is %. Thick used by plate is 12 cm as according to calculation writer and also from field. Bone distance grade on slab land;ground is D 10-100 for the direction of X and D 10-150 for the direction of Y, while suspended land;ground used D 10-150 for the direction of X and Y.Keyword : Tes Sand cone, slab on great, suspendedAbstrak Banyak cara untuk dapat mengetahui kepadatan tanah. Salah satu cara adalah dengan test sand cone sesuai dengan pengujian yang dilakukan pada pembangunan gedung sebaguna Politeknik Negeri Balikpapan. Test ini dilakukan untuk mendapatkan berat volume tanah kering pada tanah asli maupun pada tanah hasil suatu pekerjaan pemadatan, serta untuk mengetahui perbedaan penulangan plat lantai slab on grade dan suspended. Nilai berat volume tanah kering yang diperoleh melalui percobaan sand cone ini, digunakan untuk mengevaluasi hasil pekerjaan pemadatan dilapangan yang dinyatakan dalam Derajat bPemadatan (Degree of Compaction) dalam satuan % dengan nilai minimum 95 %. Tebal plat yang digunakan adalah 12 cm sesuai dengan perhitungan penulis maupun dari lapangan. Jarak tulangan pada tanah slab on grade adalah D 10-100 untuk arah X dan D 10- 150 untuk arah Y, sedangkan pada tanah suspended digunakan D 10-150 untuk arah X dan Y. Kata kunci : Tes sand cone, slab on great, suspended